Visual text arranger - Abdul Ghani, Che An (Universiti Putra Malaysia Press, 2016)
Visual language has been employed since early history till the present and is an integral part of human daily endeavours. According to the Visual Language Theory (Marriot & Meyer, 1998), the dynamics of visual language influence on humans is infinite. Based on this theory and the endless possibilities it can offer, the visual approach is adopted widely in the field of education and in the field of language acquisition.